Consolidate, conceptualize, contextualise: key learnings for future intervention acceptability research with young people in Africa. (15th December 2022) - Casale, Marisa; Yates, Rachel; Gittings, Lesley; Haupt Ronnie, Genevieve; Somefun, Oluwaseyi; Desmond, Chris
ABSTRACT: Acceptability has become a key consideration in the development, evaluation and implementation of health and social interventions. This commentary paper advances key learnings and recommendations for future intervention acceptability research with young people in Africa, aimed at supporting the achievement of developmental goals. It relates findings of the adolescent acceptability work conducted within the Accelerate Hub, since mid 2020, to broader inter-disciplinary literatures and current regional health and social priorities. We argue that, in order to strengthen the quality and applied value of future acceptability work with young people, we need to do three things better. First, we need to consolidate prior findings on acceptability, within and across intervention types, to inform responses to current public health and social challenges and further the conceptual work in this area. Second, we need to better conceptualise acceptability research with young people, by developing stronger conceptual frameworks that define acceptability and its constructs, and predict its relationship with intervention engagement. Third, we need to better contextualise findings by considering acceptability data within a broader social and political context, which in turn can be supported by better conceptualisation. In this paper we describe contributions of our work to each of these three inter-connected objectives, and suggest ways in which they may be taken forward by researchers and practitioners. These include aggregating evidence from past interventions to highlight potential barriers and enablers to current responses in priority areas; involving key actors earlier and more meaningfully in acceptability research; further developing and testing behavioural models for youth acceptability; and working collaboratively across sectors towards programmatic guidance for better contextualisation of acceptability research. Progress in this field will require an inter-disciplinary approach that draws from various literatures such as socio-ecological theory, political economy analysis, health behaviour models and literature on participatory research approaches.